2011
DOI: 10.1038/modpathol.2010.222
|View full text |Cite
|
Sign up to set email alerts
|

VHL mutations and dysregulation of pVHL- and PTEN-controlled pathways in multilocular cystic renal cell carcinoma

Abstract: Multilocular cystic renal cell carcinoma is a rare renal cell carcinoma with an excellent prognosis. To clarify the relationship with typical clear cell renal cell carcinoma, we evaluated 15 cases of multilocular cystic renal cell carcinomas diagnosed according to the 2004 WHO classification. Von Hippel Lindau (VHL) gene mutations were determined by whole genome amplification and direct sequencing. Carbonic anhydrase 9 (CAIX), a hypoxiainducible factor (HIF) target, paired box gene 2 (PAX2), cyclin-dependent k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 36 publications
(36 reference statements)
2
33
1
1
Order By: Relevance
“…In a recent study, VHL mutations were identified in 3 of 12 tumors (25%), and the tumor cells, in most cases, were strongly reactive to PAX2 and CAIX, similar to typical, low-grade clear cell RCC. 44 These findings are consistent with the concept of multilocular cystic RCC being a variant of clear cell RCCs. In line with the minimal tumor burden present in these tumors, prognosis is excellent; there was no recurrence or metastases on mean follow-up of more than 6.5 years in a more-recent study.…”
Section: Predominantly Cystic Renal Tumorssupporting
confidence: 79%
“…In a recent study, VHL mutations were identified in 3 of 12 tumors (25%), and the tumor cells, in most cases, were strongly reactive to PAX2 and CAIX, similar to typical, low-grade clear cell RCC. 44 These findings are consistent with the concept of multilocular cystic RCC being a variant of clear cell RCCs. In line with the minimal tumor burden present in these tumors, prognosis is excellent; there was no recurrence or metastases on mean follow-up of more than 6.5 years in a more-recent study.…”
Section: Predominantly Cystic Renal Tumorssupporting
confidence: 79%
“…The consequences of the mutations of the VHL gene are discussed in Sections 3 and 6. Recently, mutations of the VHL gene have been reported in multilocular cystic renal cell carcinoma and confirm the hypothesis that multilocular cystic renal cell carcinoma represent a subtype of clear cell renal cancer [54]. The relationship of leiomyomatous renal cell carcinoma and clear cell papillary renal cancer based on the presence or absence of VHL mutation and/or 3p losses is currently controversial.…”
Section: Cytogenetic and Molecular Alterations In Renal Cell Carcinommentioning
confidence: 73%
“…10 Mutations of the VHL (von Hippel-Lindau) gene have also been detected in multilocular cystic renal cell carcinoma. 17 In contrast, clear cell papillary renal cell carcinoma has been found to lack both of these abnormalities, 2,5,7,8 lending further support to the distinction between the two lesions. Another differential diagnostic consideration for a tumor composed of compact and acinar arrangements of clear cells with a prominent cystic component is cystic clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 93%